075 Predictors of adaptive functioning in children with tourette syndrome attending a specialist clinic. (December 2018) - Taylor, C; Mitchell-Blake, T; Kharod, A; McFarlane, F; Heyman, I; Stark, D; Murphy, T
Abstract : Introduction: Tourette Syndrome (TS) is a neurological condition affecting around 1% of children in the general population, with high rates of psychiatric co-morbidity and an increased likelihood of cognitive difficulties and specific learning disorders (Dykens et al. 1990). There is a paucity of research investigating the adaptive functioning of young people with TS. Adaptive behaviours refer to a person's ability to manage everyday life demands and personal independence skills, relative to their expected age group. It is important to identify these deficits early, to support children with TS in their daily lives. To date, no studies have examined how neuropsychological functioning and co-morbid neurodevelopmental conditions predict adaptive behaviour in TS. This study aimed to investigate predictors of adaptive behaviour for children with a diagnosis of TS. Methods: Children (n=69) were selected from a specialist Tourette syndrome clinic, attending between 2011 and 2014. Adaptive behaviour was the dependent variable, measured using the Vineland Adaptive Behaviour Scales – 2nd Edition. Independent variables included IQ, number of co-morbid conditions, motor skills and executive functioning. Parametric and non-parametric tests were used to assess predictors of adaptive behaviour. Results: 30% of the sample had TS only, 70% had ≥1 additional psychiatric diagnoses, 22% had ASD, 37% Specific learning disorders and 3% LD. An ADHD diagnosis and ≥2 co-morbidities predicted poorer adaptive behaviour. Both executive functioning scores and specific aspects of IQ (perceptual reasoning) significantly predicted adaptive behaviour and accounted for 52% of the variance in scores. Discussion: Psychiatric co-morbidity, poor executive functioning skills and poor perceptual reasoning are important predictors of adaptive functioning in TS populations. Executive functioning was the strongest predictor of adaptive functioning in this sample, consistent with previous findings of a relationship between ADHD and executive function (Sjowall, et al, 2012). Clinical implications and suggestions for intervention and further research are discussed.